Deoxygenation in Marginal Seas of the Indian Ocean - Naqvi, S. Wajih A. (Frontiers in Marine Science, 2021)
This article describes oxygen distributions and recent deoxygenation trends in three marginal seas – Persian Gulf and Red Sea in the Northwestern Indian Ocean (NWIO) and Andaman Sea in the Northeastern Indian Ocean (NEIO). Vertically mixed water column in the shallow Persian Gulf is generally well-oxygenated, especially in winter. Biogeochemistry and ecosystems of Persian Gulf are being subjected to enormous anthropogenic stresses including large loading of nutrients and organic matter, enhancing oxygen demand and causing hypoxia (oxygen < 1.4 ml l–1) in central and southern Gulf in summer. The larger and deeper Red Sea is relatively less affected by human activities. Despite its deep water having remarkably uniform thermohaline characteristics, the central and southern Red Sea has a well-developed perennial oxygen minimum at mid-depths. The available data point to ongoing deoxygenation in the northern Red Sea. Model simulations show that an amplified warming in the marginal seas of the NWIO may cause an intensification of the Arabian Sea oxygen minimum zone (OMZ). Increases in particulate organic carbon and decreases in oxygen contents of the outflows may also have a similar effect. In the Andaman Sea, waters above the sill depth (∼1.4 km) have characteristics similar to those in the Bay of Bengal, including an intense OMZ. As in the case of the Bay of Bengal, oxygen concentrations within the Andaman Sea OMZ appear to have declined slightly but significantly between early 1960s and 1995. The exceedingly isothermal and isohaline water that fills the deep Andaman Basin is also remarkably homogenous in terms of its oxygen content. A very slight but statistically significant decrease in oxygen content of this water also seems to have occurred over three decades preceding 1995. New information is badly needed to assess the extent of further change that may have occurred over the past 25 years. There have been some reports of coastal “dead zones” having developed in the Indian Ocean marginal seas, but they are probably under-reported and the effects of hypoxia on the rich and diverse tropical ecosystems – coral reefs, seagrasses, and mangroves – in these seas remain to be investigated.